Analisis Pengaruh Strategi pemasaran UMKM Berdasarkan Kualitas Produk, Harga dan Promosi Terhadap Keputusan Pembelian Menurut Prespektif Ekonomi - Eli Achmad Mahiri; Abdul Hakim; Engkun Kurnadi (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
This study aims to find out how the analysis of the influence of MSME marketing strategies based on product quality, price and promotion on purchasing decisions according to an economic perspective in maintaining business during the Covid-19 period in Yook Majalengka's Consumer Goods Salad food. This study uses a survey method with a descriptive analysis approach and verification. The data collection technique used is using a questionnaire. The population of this research is the many consumers of Salad Yook Majalengka. The sample used in this study was 100 respondents with the sampling technique used was incidental sampling. The measurement scale in this study uses a Likert scale. Data analysis used is classical assumption test, multiple linear regression analysis, coefficient of determination analysis and statistical F test. Hypothesis testing in this study used a partial hypothesis test with t test. Based on the results of this study indicate that: Product Quality has a positive and significant effect on Purchase Decisions, Price has a positive and significant influence on Purchase Decisions and Promotion has a positive and significant influence on Purchase Decisions.